Improving Mathematics Learning Outcomes in Systems of Linear Equations in Two Variables Using the Problem-Based Learning Model - Rahmat Rahmat; Ismail Djakaria; Novianita Achmad (Research in the Mathematical and Natural Sciences, 2026)
This study aims to improve students' mathematics learning outcomes on Systems of Linear Equations in Two Variables (SLETV) through the implementation of the Problem-Based Learning (PBL) model. This type of research is Classroom Action Research (CAR) conducted at SMP Negeri 1 Suwawa during the even semester of the 2024/2025 academic year, with 31 eighth-grade students (class VIII-B) as subjects. The research took place in a single cycle consisting of four meetings (three learning process meetings and one final test meeting). The instruments used included Lesson Plans, Student Worksheets, observation sheets for teacher and student activities, and learning achievement tests. Observation results indicated that the percentage of teacher activity in the "good" and "very good" categories increased from 63.6% in Meeting 1 to 90.9% in Meeting 3, with an overall average of 75.7%. The percentage of student activity in the "good" and "very good" categories increased from 59.1% in Meeting 1 to 90.9% in Meeting 3, with an overall average of 77.2%. Learning test results showed that among the 25 students who took the evaluation, 19 students achieved mastery (76%), thereby meeting the established classical success indicator (>= 75%). Thus, the application of the PBL model is effective in improving students' mathematics learning outcomes on SLETV.